-(2x-5)-(x-7)=2

Simple and best practice solution for -(2x-5)-(x-7)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x-5)-(x-7)=2 equation:


Simplifying
-1(2x + -5) + -1(x + -7) = 2

Reorder the terms:
-1(-5 + 2x) + -1(x + -7) = 2
(-5 * -1 + 2x * -1) + -1(x + -7) = 2
(5 + -2x) + -1(x + -7) = 2

Reorder the terms:
5 + -2x + -1(-7 + x) = 2
5 + -2x + (-7 * -1 + x * -1) = 2
5 + -2x + (7 + -1x) = 2

Reorder the terms:
5 + 7 + -2x + -1x = 2

Combine like terms: 5 + 7 = 12
12 + -2x + -1x = 2

Combine like terms: -2x + -1x = -3x
12 + -3x = 2

Solving
12 + -3x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3x = 2 + -12

Combine like terms: 12 + -12 = 0
0 + -3x = 2 + -12
-3x = 2 + -12

Combine like terms: 2 + -12 = -10
-3x = -10

Divide each side by '-3'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| -10+d=9 | | -x/4-10=-22 | | 96=-8(n-7) | | -3x-2(9+5x)=13-3(2x-3) | | 3(3w-2)=2(3w+3) | | 3(-7-7b)=-189 | | 2z-13=-8z+27 | | 6(1-8a)+7(3a+8)=-73 | | 2x+40=x+2y | | 15/100=23/x | | (4y+8)-(4+3y)=8 | | 4x^2-10x+7=0 | | 6a^2-3a+a-2a^2= | | 9y+27=-72 | | -x/2+3=-12 | | 92=6(r+2)+4r | | 3y-1/2=z | | 90=6(3x+1)-6x | | 5x-12+3x+6=72 | | -40+8=-10+-24 | | 4x^6-3y^4+6x^6+6y^4= | | -2=5+1x | | x/3-9=10 | | 2t+3+3t-4t=4+2 | | 4x^6-3y^4+6x^6y^4-6x^6+6y^4= | | -x-2=6 | | x/2-13=11 | | -53+29=x | | x^2+16=-5 | | -53+23=x | | -53+=x | | 5x^2+5y^2=25 |

Equations solver categories